UJI AKTIVITAS ANTIOKSIDAN EKSTRAK ETANOL DAUN BAWANG MEKAH (Eleutherine americana Merr.)TERHADAP GAMBARAN HISTOPATOLOGI PARU-PARU TIKUS (Rattus norvegicus) WISTAR JANTAN PASCA PAPARAN ASAP ROKOK - ., Hafidzah Ramadhaniyah Al Idrus (Jurnal Mahasiswa Farmasi Fakultas Kedokteran UNTAN, 2014)
Exposure to cigarette smoke is one of the exogenous free radicals. Exposure tocigarette smoke is associated with lung inflammation, oxidative stress and lipidperoxidation. Compounds that can inhibit the oxidation reaction by binding free radicalsknown as antioxidants. Eleutherine americana Merr. leaves has an antioxidant activity ininvitro study. The aim of this work was to study E.americana leaves as a naturalantioxidant that reduce the level of lung damage from exposure to cigarette smoke inmale wistar rats and study effective dose of E.americana leaves to reduce the level oflung damage. Â The leaves of E.americana extracted by maceration method for 6 daysusing ethanol 70%. Rats were divided into six groups of four animals each : exposed toambient air (GroupA), exposed to cigarette smoke (Group B), exposed to cigarette smokeand treated with ethanol extract of E.americana leaves at dose 45mg/kg bw, 90mg/kg bw,180mg/kg bw (Group C,D,E), exposed to cigarette smoke and treated with vitamin E doseÂ 18mg/kg bb(Group F). All rats were treated for 14 days using 3 cigarettes non filteredeach day by using a smoking chamber. After 14 days rats were killed. Right lungs wereremoved for histopathology. The results showed that dose 45mg/kg bw, 90mg/kg bw,180mg/kg bw can reduce the level of lung damage to the enlarge of alveolar, thickeningof the alveolar wall and inflammatory cell infiltration. Dose 180mg/kg bw as an effectivedose to reduce the level of lung damage that compare to normal control.Â Keywords : Antioxidant, Eleutherine americana, Lung histopathology, Cigarettesmoke